What’s It Worth? Estimating the Potential Value of Early Warnings of Cyanobacterial Harmful Algal Blooms for Managing Freshwater Reservoirs in Kansas, United States - Pindilli, Emily J.; Loftin, Keith (Frontiers in Environmental Science, 2022)
Cyanobacterial blooms are an issue drawing increasing concern in freshwater lakes in the United States due to the real and sometimes perceived harms they can cause through cyanotoxin production or other effects. These type of blooms are referred to as cyanobacteria harmful algal blooms (cyanoHABs) when effects from cyanotoxin exposure can potentially lead to human health effects through recreation and consumption of drinking water and may impact fisheries, wildlife, domestic pets, and livestock. Characterizing the societal impacts of toxin production, exposure, and effects and the estimating the potential value of information of an early warning system can inform and support freshwater lake management decisions and future research directions. A Bayesian decision tree analysis was utilized to identify uses, users, and benefits of the information provided by this research. Specifically, the potential value related to a cyanoHAB early warning system was analyzed that would provide information two additional days earlier relative to cyanoHAB occurrence above a threshold of concern. The evaluation considers the application of this information for freshwater lake management - whether or not to post an advisory or warning at a reservoir to recreational water contact. The model was parameterized with data from the state of Kansas and the value of avoided foregone recreation and avoided health effects was derived. The estimated annual value of information ranges between $565 thousand to $2.3 million (2018USD) for the state of Kansas alone based on provided assumptions. The results demonstrate a lower bound of the value of a cyanoHAB early warning system and suggest additional research to understand the use and value of this information could support research prioritization and further illustrate the return on research investment. This analysis does not incorporate the full suite of potential societal costs that may be associated with a cyanoHAB event such as drinking water treatment, impacts to irrigation, or power generation.